Analysis of Student's Misconceptions in Static and Dynamic Electricity Physics Using the Three Tier Test - Nur Untoro; Gupita, Nawanda De; Yanti, Alya Rahma (Impulse: Journal of Research and Innovation in Physics Education, 2022)
Physics is one of the subjects that is considered difficult, this assumption is reinforced by students who experience misconceptions, some even do not understand the concept. This study aims to find out students' misconceptions about static electricity and dynamic electricity. The research method is qualitative, with research subjects consisting of 20 students from class XII. The test instrument used consisted of 10 static and dynamic electricity questions self-made with content validation results of 0.96, empirical validity of 1.01, and reliability of 0.8 using the three-tier test method. The data collection techniques used in the form of tests. The results of the study showed that 33.5% of students experienced misconceptions, the value was categorized as moderate. Meanwhile, 29.5% did not understand the concept and 35% understood the concept. Although the level of misconception is categorized as moderate, it still has to be an evaluation.